2022
DOI: 10.1186/s13098-022-00902-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control among type 2 diabetes patients in sub-Saharan Africa from 2012 to 2022: a systematic review and meta-analysis

Abstract: Background There is an increased burden of diabetes globally including in sub-Saharan Africa. The literature shows that glycaemic control among type 2 diabetes patients is poor in most countries in sub-Saharan Africa. Understanding the factors influencing glycaemic control in this region is therefore important to develop interventions to optimize glycaemic control. We carried out a systematic review to determine the prevalence and factors associated with glycaemic control in sub-Saharan Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 131 publications
2
19
0
Order By: Relevance
“…Studies done in different parts of Sub-Saharan Africa revealed that the majority of DM patients had poor glycemic control ( 8 , 9 ). Similarly, different hospital-based studies done in Ethiopia showed that the burden of poor glycemic control ranged 52% -80% ( 10 12 ), and diabetes-related burden is expected to be high.…”
Section: Introductionmentioning
confidence: 99%
“…Studies done in different parts of Sub-Saharan Africa revealed that the majority of DM patients had poor glycemic control ( 8 , 9 ). Similarly, different hospital-based studies done in Ethiopia showed that the burden of poor glycemic control ranged 52% -80% ( 10 12 ), and diabetes-related burden is expected to be high.…”
Section: Introductionmentioning
confidence: 99%
“…8 A recent systematic review of the studies on glycaemic control found: younger and older age, gender, poor socio-economic conditions, place of living, positive family history of diabetes, longer duration of diabetes, treatment modalities and effects, alcohol consumption, smoking presence of comorbidities or complications, and poor management were associated with poor glycaemic control. 9 Contrarily, high diabetes health literacy, positive perceived family support, adequate coping strategies, dietary adherence, exercise practice, attendance of follow-up appointments, and medication adherence were associated with good glycaemic control. 9 In the DRC, very few studies have investigated poor glycaemic control among persons/patients living with type 2 diabetes, as high as 86% in the nearby province of Kwilu 10 and 79.9% in Kinshasa.…”
Section: Intrdoductionmentioning
confidence: 99%
“…9 Contrarily, high diabetes health literacy, positive perceived family support, adequate coping strategies, dietary adherence, exercise practice, attendance of follow-up appointments, and medication adherence were associated with good glycaemic control. 9 In the DRC, very few studies have investigated poor glycaemic control among persons/patients living with type 2 diabetes, as high as 86% in the nearby province of Kwilu 10 and 79.9% in Kinshasa. 11 Only a few reported factors were found to be associated with glycaemic control among persons living with type 2 diabetes mellitus in the DRC.…”
Section: Intrdoductionmentioning
confidence: 99%
See 2 more Smart Citations